STUDY OF CONSUMER ACCEPTANCE ON CATFISH (Pangasius hypophthalmus) CAKE WITH BROCCOLI (Brassica oleracea)ADDITION - M Lumbantobing, Julio; Sari, N. Ira; Sumarto, Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis study aims to determine the level of consumer acceptance on catfish (Pangasius hypophthalmus) cake with broccoli addition and to obtain the best nutritional value. The method used in this research was an experimental method that was the processing of catfish cake with broccoli addition consisting of 0, 10, 20, and 30%. Catfish cake with the addition of broccoli was significantly affected by organoleptic values (taste, texture, color, and aroma), protein, ash, fiber content, and total bacterial colonies meanwhile were not significantly affect water content at 95% of confidence level. Based on the results of research the addition 10% of broccoli on catfish cake was most favorable by consumer acceptance, as many as 77 panelists (96.25%) with the characteristic of the taste of broccoli flour was rather tasted (6.75), chewy texture (7.52), mottled green appearance (6.67), the broccoli flour aroma (6.62), while water content (25.18%), protein content (10.18%), ash content (1.45%), crude fiber content (5.02%) and total bacterial colonies 2.2 × 103cells/gram.Keywords: fish cake, catfish, broccoli, consumer acceptance.